STUDY OF SILICON-INSULATOR STRUCTURE DEFECTS BASED ON ANALYSIS OF A SPATIAL DISTRIBUTION OF A SEMICONDUCTOR WAFERS’ SURFACE POTENTIAL - R. I. Vorobey; O. K. Gusev; A. L. Zharin; A. N. Petlitsky; V. A. Pilipenko; A. S. Turtsevitch; A. K. Tyavlovsky; K. L. Tyavlovsky (Приборы и методы измерений)
The matter of the study is application of contact potential difference and band bending visualization technique based on Kelvin–Ziesman technique to the non-destructive testing and defects study of a silicon-insulator structure. Experiments were held using a thermally oxidized boron-doped silicon wafer. Visualized defect distribution map is in a good agreement with a preliminary data on defectproducing factors. Results compared to ellipsometry data show that CPD visualization data is not influenced by presence and thickness of insulating layer.